Probenecid Inhibits NLRP3 Inflammasome Activity and Mitogen-Activated Protein Kinases (MAPKs) - Les P. Jones; David E. Martin; Jackelyn Murray; Fred Sancilio; Ralph A. Tripp (Biomolecules)
Probenecid has long been a versatile drug in pharmacological therapies, primarily known for blocking active tubular secretion in the kidney, affecting both endogenous substances like uric acid and exogenous ones like penicillin. Beyond its renal applications, probenecid has shown capabilities in crossing the blood–brain barrier and modulating the activity of various membrane channels and transporters. This compound has emerged as a potent antiviral agent, demonstrating efficacy against multiple viruses, including influenza, COVID-19, and RSV. Clinical trials with COVID-19 patients have confirmed its antiviral potential, sparking further investigation into its mechanisms of action. This study explores probenecid’s significant anti-inflammatory properties, focusing on its ability to inhibit inflammasome activation. Our study aims to unravel the anti-inflammatory effects of probenecid on the NLRP3 inflammasome and MAPK signaling pathways using murine macrophages as a relevant inflammation model. We reveal that probenecid treatment blocks JNK and ERK signaling without affecting p38 MAPK, suppressing NLRP3 inflammasome activation. Additionally, probenecid does not affect NFκB-directed protein expression, although it efficiently inhibits NLRP3 inflammasome outputs, e.g., IL-1β and pyroptosis. These results indicate probenecid’s potential therapeutic applications.